MICROELEMENTS: HISTORY AND CONTEMPORARY - Ерстенюк, Г. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Resulted data in relation to development of study about microelements by prominent Ukrainians – academician Vernadsky V. I. and his follower by an academician Babenco G. O. Problem “Microelements and health man” remains actual and today, important there are researches devoted to the biochemical mechanisms of development of microelements and searches of ways of prophylaxis and correction of these being.